Risk-Association of DNA Methyltransferases Polymorphisms with Gastric Cancer in the Southern Chinese Population - Yang, Xue-Xi (Molecular Diversity Preservation International (MDPI), 2012)
DNA hypomethylation and/or hypermethylation are presumed to be early events in carcinogenesis, and one or more DNA methyltransferases (DNMTs) have been suggested to play roles in carcinogenesis of gastric cancer (GC). However, there have been no systematic studies regarding the association between DNMT gene polymorphisms and GC risk. Here, we examined the associations of 16 single nucleotide polymorphisms (SNPs) from DNMT1 (rs2114724, rs2228611, rs2228612, rs8101866, rs16999593), DNMT2 (rs11695471, rs11254413), DNMT3A (rs1550117, rs11887120, rs13420827, rs13428812, rs6733301), DNMT3B (rs2424908, rs2424913, rs6087990) and DNMT3L (rs113593938) with GC in the Southern Chinese population. We assessed the associations of these 16 SNPs with GC in a case-control study that consisted of 242 GC cases and 294 controls, using the Sequenom MALDI-TOF-MS platform. Association analyses based on the χ(2) test and binary logistic regression were performed to determine the odds ratio (OR) and 95% confidence interval (95%CI) for each SNP. We found that rs16999593 in DNMT1, rs11254413 in DNMT2 and rs13420827 in DNMT3A were significantly associated with GC susceptibility (OR 1.45, 0.15, 0.66, respectively; 95% CI 1.00–2.11, p = 0.047; 0.08–0.27, p < 0.01; 0.45–0.97, p = 0.034, respectively, overdominant model). These results suggested that DNMT1, DNMT2 and DNMT3A may play important roles in GC carcinogenesis. However, further studies are required to elucidate the mechanism.